Composition effects on pore structure of transitional shale: A case study of the upper Carboniferous Taiyuan Formation in the eastern uplift of the Liaohe Depression, China. (December 2019) - Zhang, Qin; Xiong, Xiaolin; Pang, Zhenglian; Liu, Renhe; Liang, Feng; Liang, Pingping; Guo, Wei; Zhang, Jinchuan
Abstract: Transitional shale is very different from marine shale with respect to mineral composition and pore structure. Insights into the effects of rock composition on pore structure can aid understanding of the storage and migration mechanisms of shale gas in a reservoir. To investigate the compositional effects on pore structure, a combination of geochemical and petrophysical experiments were conducted on four bulk shale samples and their corresponding extracted organic matter (OM) and clay mineral samples. The experimental results show that the removal of OM using H2 O2 during clay mineral extraction oxidizes and removes pyrite and siderite from the samples while other inorganic phases remain unaffected. OM hosted more abundant micropores compared with clay minerals, while mesopores and fine-macropores are dominant in clay minerals. Effects of the OM and clay minerals on pore volume and surface area are quantitatively evaluated on the basis of weight-normalized pore-size distribution (PSD) curves of extracted OM and clay mineral samples. In terms of the CO2 adsorption, contribution from OM and clay minerals to micropore volume (MIV) are 19.43–32.92% and 18.75–39.05% respectively, and to micropore surface area (MIS) are 19.30–32.28% and 16.42–35.72%. Other minerals (other than organic matter and clay minerals) account for 34.29–48.93% of the MIV and 39.75–52.98% of the MIS. N2 adsorption results reveal that the pore volume and surface area are mainly attributable to the clay minerals, providing 54.37–80.75% of the BJH pore volume (BJHV) (average 65.83%) and 70.68–87.04% of the BET surface area (BETS) (average 78.71%). The primary medium for pore development in marine shale is OM, whereas pores in the transitional shale are mostly found in the clay and other inorganic minerals. Therefore, the hydraulic fracturing design and drilling-related operations involved in the exploitation of transitional shale gas should be appropriately adjusted and improved in order to accommodate intrinsic characteristics of the transitional shale gas reservoir. Highlights: Organic matter(OM) and clay minerals were isolated from shale samples. Pore size distribution of bulk, and corresponding OM and clay samples were tested. Composition effects on pore structure were quantitatively calculated.